A preliminary investigation of cultivated and wild species of Luffa for oil and protein contents. Issue 1 (April 2014) - Prakash, Krishna; Radhamani, Jalli; Pandey, Anjula; Yadav, Sangita
<x content-type="archive" xml:space="preserve">Abstract</x> Seeds of wild and cultivated species of Luffa were studied to determine the variability in morphological (seed size, colour, seed-coat surface and 100-seed weight) and biochemical (oil and protein) characteristics. A total of 80 accessions of three cultivated species (71 accessions) and three wild species (9 accessions) of Luffa under the present investigation from diverse regions (12 states of five regions) of India showed variations in seed size, colour, seed-coat surface, 100-seed weight, and seed protein and oil contents both within the accessions of the same species and between different species. Significant variability in seed morphological traits was observed. Both seed oil and soluble seed protein contents were highest in some accessions of the cultivated species (25–27% oil and 8–10% protein, respectively, on a fresh seed weight basis). Using the 2D scatter plot diagram derived from the principal components analysis, the morphological and biochemical traits of the 80 Luffa accessions classified the wild species into one cluster (cluster I) and the cultivated species into a second major cluster (cluster II). The present investigation on the correlation between seed morphology and biochemical traits in the cultivated and wild species of Luffa can help in identifying the genotypes of Luffa species with valuable traits for further exploring the potential of this valuable crop as a source of edible oil, food and fodder in edible seed types or as a source of industrial oil/biodiesel in non-edible seed types. The protein-rich seed could be further explored to be utilized in the fortification of food products for value addition.